El periodismo social media como herramienta del quehacer periodístico actual - Pasmay Pesantes, Fernanda Lisbeth (2018)
The main objective of this research work is to analyze the loyalty process in digital information sources in the investigative web journalism that I implement daily "El Telégrafo in the Odebrecht case. The headlines issued by the newspaper El telégrafo in the context of the Odebrecht case were taken into consideration, and their response interaction by the public towards their state ideology was contrasted…….